IEEE 802.15.4 for wireless sensor networks: a technical overview - Koubâa, Anis (2014)
Low-rate low-power consumption and low-cost communication are the key points that lead to the specification of the IEEE 802.15.4 standard. This paper overviews the technical features of the physical layer and the medium access control sublayer mechanisms of the IEEE 802.15.4 protocol that are most relevant for wireless sensor network applications. We also discuss the ability of IEEE 802.15.4 to fulfil the requirements of wireless sensor network applications.